2003
DOI: 10.1111/j.1741-3737.2003.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Between Marital Quality and Job Satisfaction: Long‐Term Patterns and Gender Differences

Abstract: ࡗ Spillover Between Marital Quality and Job Satisfaction: Long-Term Patterns and Gender DifferencesWe used data from a 12-year panel survey of a nationally representative sample of married individuals (not couples) and structural equation modeling to investigate the process of spillover between marital quality (satisfaction and discord) and job satisfaction among married individuals. We considered three questions: whether job satisfaction and marital quality are related over the long term, whether influence fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
97
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(120 citation statements)
references
References 41 publications
16
97
1
6
Order By: Relevance
“…The results also showed that marital satisfaction had a positive, significant relationship with job satisfaction (r=0.208, P<0.01), which is consistent with those of Cullen and Dymarty (2013), Rogers and May (2011), and Zandi Pour and Momeni Javid (2014). Family and marital satisfaction are associated with numerous factors outside families including job.…”
Section: Discussionsupporting
confidence: 78%
“…The results also showed that marital satisfaction had a positive, significant relationship with job satisfaction (r=0.208, P<0.01), which is consistent with those of Cullen and Dymarty (2013), Rogers and May (2011), and Zandi Pour and Momeni Javid (2014). Family and marital satisfaction are associated with numerous factors outside families including job.…”
Section: Discussionsupporting
confidence: 78%
“…Commitment stemming from the parental role is associated with career satisfaction and performance, relates to a sense of enhancement, which reduces stress and strengthens positive outcomes. In addition, satisfaction with marriage has a significant relationship with job satisfaction [27] [28]. Experienced work/family enrichment may also have practical implications in terms of reducing the work absences incidence [29].…”
Section: Work-family Interface: the Positive And Negative Consequencesmentioning
confidence: 99%
“…Heller, Judge, and Watson (2002) also tested the spillover hypothesis and found that life satisfaction and job satisfaction are correlated, but that this correlation drops when personality variables are statistically controlled. In a 12-year panel study, Rogers and May (2003) found that marital quality and job satisfaction are related over time. Similarly, Kang (2001) found spillover from the job to marriage.…”
Section: Spillover From Workmentioning
confidence: 99%